Detection of permafrost in shallow bedrock areas with the opposing coils transient electromagnetic method - Yang, Guiqian; Xie, Changwei; Wu, Tonghua; Wu, Xiaodong; Zhang, Yuxin; Wang, Wu; Liu, Guangyue (Frontiers in Environmental Science, 2022)
The transient electromagnetic method (TEM) is a geophysical method for detecting underground geological bodies by following the principle of electromagnetic induction, which has been widely used in permafrost exploration. In the practical applications of the TEM to investigate permafrost, it is found that in certain areas with shallow buried bedrock, the electrical resistivity near the surface cannot be obtained, and both frozen soil and underground bedrock exhibit a high electrical resistivity, so it is difficult to determine the distribution characteristics of the permafrost thickness. Based on this background, by analyzing measured data, it is considered that the reason for this situation is that the noise superposition effect generated by the receiving coil under the action of the primary field forms a shallow detection blind area. This study uses equivalent anti-flux opposing coils to eliminate the abovementioned blind area and realize measurement in the permafrost area of Mahan Mountain in Lanzhou. The results showed that the opposing coils transient electromagnetic method (OCTEM) can clearly detect low-resistivity anomalies near the boundary and permafrost base in the Mahan Mountain area, solve the problem of the shallow detection blind area of the conventional TEM, effectively eliminate the interference caused by the primary field, and greatly improve the horizontal and vertical resolutions.